THE INFLUENCE OF KAPOK (Ceiba pentandra) SEED OIL SUPPLEMENTATION ON CELLULOLYTIC ENZYME AND RUMEN MICROBIAL FERMENTATION ACTIVITY OF LOCAL SHEEP - Widiyanto, W.; Soejono, M.; Bachruddin, Z.; Hartadi, H.; Surahmanto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
This research was conducted to study the influence of kapok seed oil (KSO) supplementation oncellulolytic enzyme and microbial fermentation activity. Sheep rumen fluid was used as enzyme sourceand inoculant, whereas carboxymethylcellulose (CMC) was used as the substrate. There were 4 levels ofKSO supplementation as treatment, i.e. : 0% (T0), 5% (T1), 10% (T2), and 15% (T3). Two measuredvariables were reduced sugar production rate and gas fermentation production. The data were analyzedby analysis of variance in completely randomized design. The result showed that reduced sugarproduction rate in T0, T1, T2 and T3 treatment groups were 2.58; 2.93; 2.08 and 1.58 mg/gCMC/minute, respectively, whereas gas production were : 15.97; 13.26; 10.54 and 7.57 mg/g CMC,respectively. Kapok seed oil supplementation up to 5% DM of cellulose substrate (CMC) did notinfluence the ruminal cellulolytic enzyme activity. The KSO supplementation level 10% - 15%decreased the ruminal cellulolytic enzyme activity.